Pengaruh Penggunaan Filter Dengan Media Arang Tempurung Kelapa, Zeloit Dan Silica Gel Terhadap Gas Yang Dihasilkan Dari Reaktor Gasifikasi - Hidayat, Arifin Fajar; , Nur Aklis, S.T., M.Eng (2017)
One of utilization of biomass energy to get an alternative energy is gasification technology. To get gases that can be use on the next process, the gases need to be cleaned. This study aimed to determine the effect of using filter on the gas produced by fluidized bed gasifier reaktor includes boilling water methods and the heat are produced. This research using Fluidized Bed reactor and variation of the filter media with Coconut Shell Charcoal, zeolite and silica gell. Retrieve data with bed media 10 kg of resin sands, 5 kg of rice husks, and boilling 2 litre of waters, and record the reactor temperature, fire temperature, and water boilling temperature every 2 minutes. The research results showed the effect of using filter media on the gas product by gasification. On unfiltered gas obtained the highest fire temperature at 589 °C, boilling water along 26 minutes and producting 1280, 584 kJ of heat. On Coconut Shell Charcoal filter obtained the highest fire temperature at 657 °C, boilling water along 16 minutes and producting 2408,944 kJ of heat. On zeolite filter obtained the highest fire temperature at 955 °C, boilling water along 16 minutes and producting 1844,795 kJ of heat. On silica gell filter obtained the highest fire temperature at 634 °C, boilling water along 20 minutes and producting 2182,861 kJ of heat. On mixtured filter obtained the highest reactor temperature at 341,03 °C, the highest fire temperature at 561 °C, boilling water along 34 minutes and producting 1844,665 kJ of heat.